Estudo das abordagens do conhecimento, representações e dos obstáculos epistemológicos em livros didáticos de química - Vicentini, Thiago Von Mulhen Ferreira (2018)
This research contains information on four collections of textbooks of the Chemical component approved in the PNLD of 2015 address the chemical knowledge, promoting requisites for the formation of mental representations, in Peirce (1974), and avoiding epistemological obstacles, in Bachelard. For this analysis, chapters of Chemical Reactions, Chemical Kinetics and Alcohol function were selected as sources of texts for the investigation, due to the importance of this knowledge for the academic level of Basic Education. The texts were analyzed qualitatively, relating the main characteristics of the essays of the chapters with the theoretical assumptions that guided the investigation. With respect to the approach of aspects of chemical knowledge and mental representations, the analysis aimed to understand convergent characteristics in the writing of the texts with the theory of Jonhstone, assumptions of Mortimer and the semiotic theory of Peirce. With regard to the epistemological obstacles, tables were built to identify and categorize the impediments identified in the texts. With the end of the analysis, it was understood that the books do not have the same properties regarding the ways of approaching chemical knowledge, and most of the texts presented deficiencies in relation to the phenomenological approach. Regarding mental representations, most of the books did not demonstrate adequate characteristics, mainly related to the First level, initial stage for the formation of a mental representation. Regarding the epistemological obstacles, a small quantity was identified, not having any relevance to impair the learning of the chemical knowledge present in the textbooks.